A Novel Multiple Interface Structure with the Segregation of Dopants in Lead‐Free Ferroelectric (K0.5Na0.5)NbO3 Thin Films. Issue 2 (1st December 2017) - Li, Chao; Wang, Lingyan; Chen, Wen; Lu, Lu; Nan, Hu; Wang, Dawei; Zhang, Yijun; Yang, Yaodong; Jia, Chun‐Lin
Abstract: Interfaces in oxides are found to possess different properties and can be engineered for modifying local structure and properties of nearby area. In this work, it is reported that the interfaces can be formed in Ba/Zr (BZ)‐doped (K, Na)NbO3 (KNN) thin films by cycles of chemical solution deposition using same precursor solution. In the films, a novel and special cross‐sectional structure is observed with periodic distribution of Ba‐rich and Zr‐rich layers. The Ba‐rich and Zr‐rich layers exhibit different strain, lattice parameters, and crystal structure, leading to an obvious effect on the general ferroelectric properties of the KNN‐based thin films. Moreover, the self‐polarization is also observed, which can be understood to originate from the formed built‐in field by layered distribution of Ba and Zr in the KNN‐BZ thin films. Abstract : A novel multiple interface structure is characterized with periodic distribution of Ba‐rich and Zr‐rich layers in lead‐free ferroelectric (K, Na)NbO3 ‐Ba/Zr (KNN‐BZ) thin films, which enhances the ferroelectricity of the KNN‐BZ thin films. The interfaces can be realized by combining multiple cycles of chemical solution deposition with the long‐range electrostatic potential effects of substrate.